Assistance in strengthening women's MSME communities through a community development and community organization approach - Galuh Aditya; Dwi Astutik; Lolanda Hamim Annisa; Gabriela Yabestania Shekinah G; Timothy Jerry Kristiyanto (Universitas Muhammadiyah Magelang, 2025)
The purpose of this community service is to address management issues from both individual and group perspectives, as well as marketing challenges. The implementation of the activity was carried out through training and mentoring using a community development and community organizer approach. The results indicate that management and marketing issues have begun to be resolved. This includes the emergence of organizational behavior awareness, awareness of continuous education, and an improved understanding of business risks and financial management. Additionally, the partners now have online promotional media, both website-based and social media, which have contributed to increased sales and enhanced brand recognition of Banyu Mili MSMEs.